Modern PHP web development with MySQL, GitHub and Heroku. (Manning Publications, 2022)
This course is designed to equip students with the skills required for creating dynamic web pages using PHP and MySQL. It further equips students with the fundamentals of PHP programming, while providing them with advanced features of the language. Immerse yourself in an end-to-end full-stack development experience, as we explore user interface design, business logic and hosting activities. Learning Development with PHP - PHP was designed to make web development easier, and many beginners find it effortless to pick up and get started with. In fact, PHP code is so easy to pick up, many non-programmers end up being able to write a PHP application in no time! This course is practical and will equip you with all you need to build a fully functional web application, add it to source control using GitHub and finally, host it on Heroku. By the end of this course, you will be able to build an attractive PHP application styled using Bootstrap 4;&nbsp,track and manage changes with GitHub ,and deploy a fully data-driven application to Heroku Cloud Hosting.